2022
DOI: 10.3390/nano12071151
|View full text |Cite
|
Sign up to set email alerts
|

Aspartic Acid Stabilized Iron Oxide Nanoparticles for Biomedical Applications

Abstract: Aspartic acid stabilized iron oxide nanoparticles (A-IONPs) with globular shape and narrow size distribution were prepared by the co-precipitation method in aqueous medium. A quantum-mechanical approach to aspartic acid optimized structure displayed negative charged sites, relatively high dipole moment, and hydrophilicity, which recommended it for interaction with iron cations and surrounding water electrical dipoles. A-IONPs were characterized by TEM, XRD, ATR-FTIR, EDS, DSC, TG, DLS, NTA, and VSM techniques.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In our previous studies, magnetic nanoparticles coated with aspartic acid (A-MNP) were prepared and tested, showing great potential for biomedical applications. Therefore, starting from these results reported by Răcuciu et al (2022) [27] regarding the synthesis and characterization of A-MNP and the study on the genotoxicity of a similar A-MNP sample, reported by Răcuciu (2020) [28], we continued the research as presented in this paper dealing with the evaluation of the A-MNP influence on maize seeds. To our knowledge, no results regarding the influence of magnetic nanoparticles coated with aspartic acid on plants have been reported.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…In our previous studies, magnetic nanoparticles coated with aspartic acid (A-MNP) were prepared and tested, showing great potential for biomedical applications. Therefore, starting from these results reported by Răcuciu et al (2022) [27] regarding the synthesis and characterization of A-MNP and the study on the genotoxicity of a similar A-MNP sample, reported by Răcuciu (2020) [28], we continued the research as presented in this paper dealing with the evaluation of the A-MNP influence on maize seeds. To our knowledge, no results regarding the influence of magnetic nanoparticles coated with aspartic acid on plants have been reported.…”
Section: Introductionmentioning
confidence: 69%
“…Nanoparticles' toxicity towards plants is species-dependent [55], being linked to the applied treatment (nanoparticle type and concentration) and to growth conditions. The A-MNP sample, used in this study, is suitable for biomedical applications due to dominant small particles with a narrow size distribution and a physical diameter of about 9.17 nm, showing good stability [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The list of commonly used electrostatic stabilizers includes citric acid, ammonium salts (cetyltrimethylammonium bromide (CTAB), tetramethylammonium (TMAOH)), sodium salt (sodium dodecyl sulfate (SDS)) or amino acids (L-lysine, aspartic acid [ 49 , 50 ], etc.).…”
Section: Fundamental Characteristics Of Magnetic Nanoparticlesmentioning
confidence: 99%
“…Developments in the construction of magnetic nanoparticles have managed their innovative usages in cell tracking, cell separation, bio sensors, enzyme immobilization, hyperthermia treatment, immunology, drug delivery vehicles (Ferrofluids), diagnosis, etc. For these applications, the perfect IOMNPs should display a trivial size (<100 nm), splendid magnetism with negligible polydispersity, safe, biodegradable eco-friendly surface crust, and extraordinary magnetization properties [9][10][11][12][13] . IOMNPs are most popular in biomedical applications due to their low cost, less toxicity, and their unique magnetic properties.…”
Section: Introductionmentioning
confidence: 99%